Propuesta curricular ambiental para mejorar el área de educación ambiental en el colegio “Gimnasio Colombo Republic (2018)
Environmental education is one of the most used tools lately to create awareness within persons belonging to a community; since this is provided, mostly in the institutions of education (schools), in this environment it works with children and adolescents, in other words, adults in formation, witb which it's easier to appropiate the knowledge since they don't present customs or ingrained habits, for this reason, it's easier to inculcate an adequate environmenral performance. The necessity of application of these tools it’s because natural resources are boasts today are deteriorating, population growth has increased consumerism, so waste generation has increased. This study was conducted within an institution of the minucipality of Soledad, called Gimnasio Colombo Republicano (GICOR), the need was perceived as within the institution wasn't covered environmental issues into the curriculum, in addition to being inside one of municipalities with higvest population density os the country and meet with a socio-economic condition of stratum one and two, the majority of it's inhabitants are displaced and settled and created neighborhoods in the form of invasion. Hauling more problems, for this reason to have people to have a clearer vision of the environmental situation and knowledge themselves can undertake campaigns to improve each of the problems.